Experimental investigation of the effect of supply airflow position, excess air ratio and thermal power input at burner pot on the thermal and emission performances in a pellet stove. (January 2023) - Sungur, Bilal; Basar, Cem
Abstract: In this study, the effect of burner pot design by changing supply airflow position at three different excess air ratios and three different thermal power inputs on thermal performance and emissions at pellet stove experimentally researched. In this context, burner pots with four different supply airflow distances of 15, 30, 60 and 75 mm above the burner pot base were designed, manufactured and performance tests were made. Considering all excess air conditions, at 6 kW, the efficiencies in the 75 mm distance showed the worst performance; at 9 kW, the 30 and 60 mm distances were better, and at 12 kW, the 30 mm distance reached the highest efficiency with the value of 80.80–89.48%. The highest CO emissions obtained at the supply airflow distance of 15 mm and λ = 1.7 conditions at 12 kW with the value of 2982 ppm. It is hard to make a general inference on the thermal and emission performances to propose optimal conditions. However, it can be said that optimal conditions for the use of the stove produce high efficiencies with low polluting emissions were in the range of 6–9 kW thermal power, λ = 1.7–2.2 excess air ratios and 30 mm supply airflow distance.